Desentralisasi Pendidikan Madrasah Melalui Otonomi Daerah Di Indonesia - Masyithoh Aini (Universitas Cokroaminoto Yogyakarta, 2022)
Regional autonomy policies in Indonesia have penetrated the world of primary and secondary education, including madrasas. As an education with religious characteristics, its impact has significance compared to equivalent general educational institutions. This can be seen from the literature review in this study. After the content is analyzed, it can be concluded that regional autonomy has provided broad freedom for madrasas in utilizing school-based management (SBM), delegation of authority, including opportunities for educational innovation. The autonomy paradigm in the field of education has spurred the movement of madrasa education to a more humane orientation of educational goals. Students are awakened to be more sensitive to participate in education that prosper together based on local religious wisdom.